FAIRS, FORMS OF EXPRESSION OF THE LOCAL IDENTITY CASE STUDY: BEIUȘ FAIR, BIHOR COUNTY, ROMANIA - Grigore Vasile HERMAN (Analele Universităţii din Oradea: Seria Geografie, 2017)
This study dwells on the role and the importance of fairs, and particularly about ”Beiuș Fair”, in conserving, promoting and capitalizing the identity of the local elements. The combined use of the observation, cartographics, analisis, deduction and historiographical methods led to the identification of the main identity elements specific to the place, namely: name, the space-time localization, the involved actors and the products that are bargained.